2019
DOI: 10.1016/j.dam.2019.07.021
|View full text |Cite
|
Sign up to set email alerts
|

On the polynomiality of finding KDMDGP re-orders

Abstract: In [6], the complexity of finding K DMDGP reorders was stated to be NP-complete by inclusion, which fails to provide a complete picture. In this paper we show that this problem is indeed NP-complete for K = 1, but it is in P for each fixed K ≥ 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The DGP is naturally cast as a search in continuous space. Depending on the graph structure, however, combinatorial search algorithms can be defined, notably via the identification of appropriate vertex orders [5,11,14]. Although DGP is NP-hard [30], these combinatorial approaches allowed to show that it is Fixed Parameter Tractable (FPT) on certain graph structures, as those arising in protein conformation [20].…”
Section: Assumptionmentioning
confidence: 99%
“…The DGP is naturally cast as a search in continuous space. Depending on the graph structure, however, combinatorial search algorithms can be defined, notably via the identification of appropriate vertex orders [5,11,14]. Although DGP is NP-hard [30], these combinatorial approaches allowed to show that it is Fixed Parameter Tractable (FPT) on certain graph structures, as those arising in protein conformation [20].…”
Section: Assumptionmentioning
confidence: 99%
“…The BP algorithm was first proposed for CTOP by Lavor et al [9], and in [3] answer set programming was shown to improve the performance of the BP algorithm for CTOP. Furthermore, DMDGP vertex orders with repeated vertices, called re-orders, are considered [10], their computational complexity is analyzed [1] and further studied in detail [11].…”
Section: Introductionmentioning
confidence: 99%
“…where f is a function f : We may furnish the set V of vertices with an ordering V = {v , ..., vn} [9,15,23,25] so that the MDGP can be solved iteratively using a combinatorial method, namely the Branch-and-Prune (BP) method [8,28]. In this situation, the MDGP is called the Discretizable Molecular Distance Geometry Problem (DMDGP) [19,20], which can be stated as follows, where we use x i instead of xv i and d i,j in place of dv i ,v j : (DMDGP) Given a simple undirected graph G = (V , E, d) in which the vertex set V is ordered as V = {v , ..., vn}, whose edges are weighted by d : E → ( , ∞), subject to the following three constraints:…”
Section: Introductionmentioning
confidence: 99%